Hyperspectral Imaging for Characterization of Lithic Raw Materials : the Case of aMesolithic Dwelling in Northern Sweden - Sciuto, Claudia; Geladi, Paul; La Rosa, Lorenza; Linderholm, Johan; Thyrel, Mikael (Lithic Technology, 2019)
This study proposes a method for the classification of lithic raw materials by means of hyperspectralimaging, a non-destructive fast analytical technique. The information potential of this approach wastested on a dwelling site dated to mid-late Mesolithic (7200–5800 BP) at Lillsjön, Ångermanland,Sweden. A dataset of lithic tools and flakes (2612 objects) made of quartz and quartzite, wasanalyzed using a shortwave infrared hyperspectral imaging system. The classification of the rawmaterials was performed applying multivariate statistical models. A random test set of 55artefacts was selected, classified according to spectral signature and divided into categoriescorresponding to different geological materials. The same test set was analyzed with EnergyDispersive X-Ray Fluorescence (ED XRF) to validate the classification. The entire dataset of lithicscollected on the site was then classified applying a SIMCA model. The distribution of items onthe site was visualized in a 3D GIS platform according to their geological characteristics tohighlight patterns that could indicate different use of the space and dynamics of raw materialssupply over time. Mobima; Bio4Energy